How Did Civil War in Syria Affect Turkey's Security Policy? - AYDIN, BÜŞRA SENA (İstanbul Kültür Üniversitesi, 2022)
One of the recent challenges in the Muslim world has been a series of demonstrations across the Middle East and North Africa, known as the "Arab Spring", started in 2010s. The protests in Tunisia in late December 2010 spurred a wave of unrest that struck Algeria, Jordan, Egypt, and Yemen, before spreading to other countries. Among these countries, Syria underwent the most intense clashes between the government and rebel forces resulted in a civil war. With the civil war, Syria has become the venue for an ethnic, religious, and sectarian war, with the involvement of neighboring countries and global powers. As a result of the war, many people died, and many were forced to migrate to other countries. As a neighbor of Syria, Turkey became the country most affected by the crisis. In addition to the direct security threat because of its 911-kilometer land border, Turkey currently hosts nearly four million Syrian refugees. This study, therefore, analyzes how Turkey's security was damaged by the crisis. The study examines recent developments in the Middle East in general and in Syria specifically. It then analyzes in detail the current political, military, social implications of the crisis for Turkey's security. Keywords: Arab Spring, Syria civil war, Turkey's security.
Suriye'deki İç Savaş Türkiye'nin Güvenlik Politikasını Nasıl Etkiledi?
▪ Yüksek lisans tezi.